Update on Treatments for Parkinson's Disease Motor Fluctuations – An International Parkinson and Movement Disorder Society Evidence‐Based Medicine Review - de Bie, Rob M. A. (2025)
Objective To update evidence-based medicine recommendations for treating motor fluctuations of Parkinson's disease (PD). Background The International Parkinson and Movement Disorder Society (MDS) Evidence Based Medicine in Movement Disorders Committee recommendations for the treatments of PD were first published in 2002 and regularly updated. The current review uses a new methodology, including the Cochrane Risk of Bias tool and a modified version of GRADE (Grading of Recommendations, Assessment, Development, and Evaluations). Methods On January 1, 2023, a literature search was conducted without date limit in the MEDLINE, Embase, and Cochrane databases using the following search terms: Parkinson disease, levodopa and, for the Embase database, randomized controlled trial (RCT). The inclusion criteria for studies were: patients with PD, on oral levodopa therapy, experiencing motor fluctuations, investigating an intervention that was (commercially) available in at least one country, study design RCT, and with a follow-up duration of at least 3 months. Results A total of 102 studies were included. Levodopa extended release, pramipexole immediate release and extended release, ropinirole immediate release, rotigotine, opicapone, safinamide, and bilateral subthalamic nucleus deep brain stimulation (DBS) were assessed as efficacious, and continuous intestinal levodopa infusion, continuous subcutaneous levodopa, continuous subcutaneous apomorphine, ropinirole prolonged release, ropinirole patch, entacapone, rasagiline, istradefylline, amantadine extended release, zonisamide, bilateral globus pallidus DBS, and pallidotomy were assessed as likely efficacious for the treatment of motor fluctuations in people with PD who are already being treated with levodopa. Conclusions There are several treatment options that can improve motor fluctuations in PD. These recommendations will assist physicians and patients in determining which intervention to use.